Effects of weighted sled towing on ground reaction force during the acceleration phase of sprint running - Kawamori, N.; Newton, R.; Nosaka, K. (Journal of Sports Sciences, 2014)
Athletes use weighted sled towing to improve sprint ability, but little is known about its biomechanics. The purpose of this study was to investigate the effect of weighted sled towing with two different loads on ground reaction force. Ten physically active men (mean ± SD: age 27.9 ± 1.9 years; stature 1.76 ± 0.06 m; body mass 80.2 ± 9.6 kg) performed 5 m sprints under three conditions; (a) unresisted, (b) towing a sled weighing 10% of body mass (10% condition) and (c) towing a sled weighing 30% of body mass (30% condition). Ground reaction force data during the second ground contact after the start were recorded and compared across the three conditions. No significant differences between the unresisted and 10% conditions were evident, whereas the 30% condition resulted in significantly greater values for the net horizontal and propulsive impulses (P < 0.05) compared with the unresisted condition due to longer contact time and more horizontal direction of force application to the ground. It is concluded that towing a sled weighing 30% of body mass requires more horizontal force application and increases the demand for horizontal impulse production. In contrast, the use of 10% body mass has minimal impact on ground reaction force.